2018
DOI: 10.1002/ejlt.201700378
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Fish Oil Oleogels Formed by Natural Waxes in Comparison With Bulk Oil

Abstract: The aim of this study is to evaluate the oleogel (or organogel) technology as a new method to prevent oxidation of fish oil by immobilizing oil and to provide useful information on oxidation of oleogels for their application in actual food products. Four different natural waxes, rice bran wax, sunflower wax, candelilla wax, and beeswax are used to prepare fish oil oleogels. Peroxide value, conjugated diene value, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are measured after storing oleogels at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 33 publications
9
49
1
2
Order By: Relevance
“…At the end of the period, the oleogel PV was unexpectedly lower than value of the oil, which could be associated to the presence of polymer structure in the oleogel that provides barrier network keeping oil far from oxygen. This finding was in agreement with data reported by Huwang et al who stated that natural waxes reduced PV of the oleogel than bulk fish oil at 35 °C due to limiting oil in the gel network during 21 days . Similarly, investigation of PV in CO and the related HPMC oleogel during 18 days at 60 °C demonstrated that polymeric oleogel had a tendency to extend oxidative stability due to the limitation in oil mobility…”
Section: Resultssupporting
confidence: 92%
“…At the end of the period, the oleogel PV was unexpectedly lower than value of the oil, which could be associated to the presence of polymer structure in the oleogel that provides barrier network keeping oil far from oxygen. This finding was in agreement with data reported by Huwang et al who stated that natural waxes reduced PV of the oleogel than bulk fish oil at 35 °C due to limiting oil in the gel network during 21 days . Similarly, investigation of PV in CO and the related HPMC oleogel during 18 days at 60 °C demonstrated that polymeric oleogel had a tendency to extend oxidative stability due to the limitation in oil mobility…”
Section: Resultssupporting
confidence: 92%
“…Instead, it is recovered from the filter cakes from the winterization process, and the oil‐tank settlings are used for animal feed with low commercial value. Several studies were developed using commercial waxes but studies of wax recovered from sunflower oil processing are scarce . Argentina produces 1.1 million metric tons of sunflower oil, and a large proportion of this oil is exported as crude oil (ranking third worldwide) .…”
Section: Introductionmentioning
confidence: 99%
“…However, oxidative stability in wax‐based organogels were affected by the types of waxes. Beeswax had some prooxidative properties compared to candelilla wax to certain extent due to the lower melting point of beeswax (Hwang et al., ). The reported onset melting temperature of organogel made of 5% (w/w) beeswax, rice bran wax, and sunflower wax with rice bran oil were 53.99, 72.5, and 66.8 °C, respectively, whereas those of crystallization temperature were 46.97, 56.71, and 62.13 °C, respectively (Doan, Walle, Dewettinck, & Patel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal characteristics including melting and crystallization points were analyzed by a differential scanning calorimeter (DSC) according to the previous method (Hwang, Fhaner, Winkler‐Moser, & Liu, ), and performed on a Perkin‐Elmer DSC 4000 (Perkin‐Elmer Corp., Norwalk, CT, USA). Samples of 7 to 8 mg were weighed in aluminum pans and sealed with covers.…”
Section: Methodsmentioning
confidence: 99%